2004
DOI: 10.1097/01.tp.0000095896.07048.bb
|View full text |Cite
|
Sign up to set email alerts
|

Donor age affects fibrosis progression and graft survival after liver transplantation for hepatitis C1

Abstract: Liver transplantation with OD grafts is associated with rapid progression of fibrosis and decreased graft survival in patients with HCV, but not in patients without HCV. OD grafts should be considered preferentially for patients without HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
123
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 30 publications
17
123
4
2
Order By: Relevance
“…identified donor age higher than 60 years as a risk factor for developing cirrhosis [HR = 1.02 (1.008-1.05)] and worse graft survival [HR = 1.05 (1.03-1.07)]. Other studies have demonstrated a relationship between accelerated fibrosis and poorer outcome in grafts from older donors [41,42] . Machicao et al [41] and Wali et al [42] reported that donors aged 50 years or more, had a median fibrosis progression rate of 2.7 units/year and time to cirrhosis of 2.2 years post transplant.…”
Section: Donor Agementioning
confidence: 90%
See 1 more Smart Citation
“…identified donor age higher than 60 years as a risk factor for developing cirrhosis [HR = 1.02 (1.008-1.05)] and worse graft survival [HR = 1.05 (1.03-1.07)]. Other studies have demonstrated a relationship between accelerated fibrosis and poorer outcome in grafts from older donors [41,42] . Machicao et al [41] and Wali et al [42] reported that donors aged 50 years or more, had a median fibrosis progression rate of 2.7 units/year and time to cirrhosis of 2.2 years post transplant.…”
Section: Donor Agementioning
confidence: 90%
“…Other studies have demonstrated a relationship between accelerated fibrosis and poorer outcome in grafts from older donors [41,42] . Machicao et al [41] and Wali et al [42] reported that donors aged 50 years or more, had a median fibrosis progression rate of 2.7 units/year and time to cirrhosis of 2.2 years post transplant. In contrast, Samonakis et al [43] found that absence of maintenance steroids and azathioprine but not donor age influenced severity of HCV recurrence.…”
Section: Donor Agementioning
confidence: 99%
“…Information from prior studies of grafts from HCVϪ donors has shown that HCV recurrence is almost universal when patients are transplanted for HCV and that certain characteristics such as donor age portend worse clinical outcomes. 17,23,24 No study has evaluated the impact of specific clinical characteristics of the donor allograft on survival outcomes in recipients of HCVϩ donor transplants, nor has a study previously evaluated fibrosis progression post-liver transplantation in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, donor age Ն50 yr has specifically been found to have a negative impact on both patient and graft survival as well as accelerating fibrosis progression and the progression to cirrhosis. [16][17][18] There have been no studies to date examining the impact of donor age on liver transplantation using HCVϩ donor livers.…”
mentioning
confidence: 99%
“…Donor age seems to influence graft survival only in HCVpositive patients. However, there is little chance that this will change, since very few transplant programs are able to pair younger donors with HCV-positive receptors [11,12].…”
Section: Donor and Receptor Factorsmentioning
confidence: 99%